Organic geochemical appraisal of limestones and shales in part of eastern Dahomey Basin, southwestern Nigeria (2004)
"The major lithostratigraphic units of the eastern Dahomey Basin are the Araromi, Ewekoro and Akinbo Formations. Field studies show that the Araromi and Akinbo Formations contain shaly facies, while the Ewekoro Formation contains essentially fossiliferous limestones. The Araromi shales are dark and bituminous, while those of the Akinbo are fissile and concretionary. Selected subsurface and outcrop samples of these lithotypes were analysed to ascertain their palaeodepositional environments and hydrocarbon prospects. Total organic carbon (TOC) of the limestones and shales range from 0.10 to 1.00 wt.% and 0.20 to 1.60wt% respectively. Bitumen yields are 896.20, 108.70 and 376.80ppm correspondingly for Araromi, Ewekoro and Akinbo Formations. Bitumen ratios are 68.70, 28.30 and 72.70mgext/g TOC respectively, for the three succeeding formations. CPI values and pristane/phytane ratios are 1.29, 1.19, 0.99 and 1.53, 1.33, 1.17, respectively for Araromi, Ewekoro and Akinbo Formations. Cross-plots of isoprenoids/n-alkanes show that the organic matter falls within the terrestrial and transitional environments. However, the fossil assemblages of the limestones made up of coralline algae, pelecypods, echinoids, gastropods and few other skeletal debris, indicate a nearshore marine environment. Organic petrography reveals preponderance of vitrinites (Type III O.M.) with subordinate inertinites (Type IV) in all the three formations. The dominance of terrestrial O.M. indicates gas rather than oil proneness of the kerogen. N-alkane profiles, plots of bitumen ratios with depth and the presence of unresolved complex mixture hydrocarbons in most gas chromatograms, indicate immature status for the kerogens. This suggests insufficient cooking of the sediments."